Transcriptional profile of gene clusters involved in the methylerythritol phosphate pathway in Bacillus subtilis 916 - Ya-jing XIAO; Tan-tan GAO; Qi PENG; Jie ZHANG; Dong-mei SUN; Fu-ping SONG (Journal of Integrative Agriculture, 2019)
The methylerythritol phosphate pathway is responsible for the biosynthesis of terpenoids, the largest class of secondary metabolites. Although the structures and functions of the proteins involved in this pathway have been well studied in Bacillus subtilis, only a few studies have reported the transcriptional profile of the genes involved. Therefore, we analyzed methylerythritol phosphate pathway genes in the genome of B. subtilis 916, which has been developed as a biological control agent against some rice diseases in China. Our results showed that methylerythritol phosphate pathway genes were distributed throughout the genome of this strain. These genes were transcribed during both the exponential and stationary phases. We further confirmed the transcription units of dxs, dxr, ispD, ispF, ipK, ispG, ispH, idi, and ispA in B. subtilis 916 through reverse transcription-PCR analyses; the results showed that these nine genes were located in seven different operons. The transcript start sites of the seven different operons were determined by 5’-rapid amplification of cDNA ends-PCR. Thus, our study provides a molecular basis at the transcriptional level for investigating homoterpene synthesis in the methylerythritol phosphate pathway of B. subtilis 916.